If 'm' and 'n' are positive integers and m+n+mn = 90 then m+n=?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
m + n = 9 0 − m n n = 9 0 − m n − m n = 9 0 − m ( n + 1 ) m ( n + 1 ) = 9 0 − n m = n + 1 9 0 − n m = n + 1 9 0 − ( n − 1 ) m = n + 1 9 1 − 1 m + 1 = n + 1 9 1 ( m + 1 ) ∗ ( n + 1 ) = 9 1 = 1 3 ∗ 7 m = 1 2 , n = 6 , o r m = 6 , n = 1 2 , a n y w a y m + n = 1 8
Dear Ivan, How 90 - n = 90 - (n - 1) ?
Enclose it in \ (.....\ ) but don't leave spaces. @Ivan Martinez
Minor mistake in line 6 and 7. It should be m = ( n + 1 ) 9 1 − ( n + 1 ) ⟹ m = n + 1 9 1 − 1
MN=72 M+n=18 M=12 N=6 Or M=6 N=12
Problem Loading...
Note Loading...
Set Loading...
m + n + m n = 9 0 . Therefore, 1 + m + n + m n = 9 1 or ( 1 + m ) ( 1 + n ) = 9 1
91 can be expressed in 2 ways only,namely 9 1 × 1 and 1 3 × 7 .
Hence, the non-negative solutions are ( m , n ) = ( 9 0 , 0 ) ; ( 0 , 9 0 ) ; ( 1 2 , 6 ) ; ( 6 , 1 2 )
But since, m and n are positive,we cannot have ( 9 0 , 0 ) and ( 0 , 9 0 ) as solutions.
In the other two solutions,sum of m and n is 1 8 .